The Determination of the Main Production Cost of Jipang Cake Using the Full Costing Method - Nurhayati, Immas; Hariansyah, M; Suharti, Titing (Jurnal Manajemen, 2020)
The purpose of this study is to determine the main of production cost using the full costing method. The full costing method is one of the methods used in determining the cost of production by taking into account all components of production costs, both fixed and variable costs so that the calculation results are more precise and detailed. This research was conducted in a group of Jipang cake craftsmen in Antajaya Village, Tanjung Sari District, Bogor Regency. The data processed in this study are primary data obtained from the source directly based on real data recorded during the practice or simulation of making Jipang cake at the research location and community service. Based on the calculation, the results of the production cost of Jipang cake based on the full costing method is Rp. 472.15 or rounded to Rp. 500 per pcs.